Gender differences in effective use of land rights in South India. (August 2022) - Dagdeviren, Hulya; Oosterbaan, Lianne
Abstract: In this article, gendered dimensions of land rights are examined for the first time with a focus on what we term as 'the effective use of land rights' with respect to land-related market transactions. The aim is to develop a more nuanced understanding of land inequality. Transactions of landed households are studied here with respect to land market (i.e. selling, purchasing and renting land) and other market exchanges that are necessary to extract the benefits from land as a productive resource (i.e. credit, labour and input markets). The research is carried out in Tamil Nadu, India. The analysis is based on primary survey data and semi-structured interviews. The findings show that female participation in land-related market transactions is associated with landownership by women, but only for specific transactions. Participation of women in land purchases, measured by the incidence of holding land titles, is greater than their participation in land sales. When women own land, their involvement in the management of farm labourers is higher but their direct access to credit and participation in agricultural inputs markets remains very limited. The Implication of these findings for national and international policy, especially for the UN Sustainable Development Goals (SDGs), is that legal reforms providing equal rights for women are essential but insufficient without open-ended efforts in multiple fronts, targeting regressive social norms and customs. Highlights: Ownership with land titles results in women using their property rights more effectively for only certain transactions. Direct involvement of women in land purchases is higher than their involvement in land sales. Women's participation in credit and agricultural input markets is lower in households where land titles belong to women. The incidence of women managing farm workers is higher in households where land titles are held by female members.